Psychometric properties of the modified Suicide Stroop Task (M-SST) in patients with suicide risk and healthy controls - Gold, Helena; Stein, Maria; Glaesmer, Heide; Spangenberg, Lena; Strauss, Maria; Schomerus, Georg; Stengler, Katarina; Brüdern, Juliane (Frontiers in Psychology, 2024)
The Cognitive Model of Suicide proposes a suicide attentional bias in individuals with suicidal thoughts and behavior (STBs). The Suicide Stroop Task (SST) was developed as a behavioral measure to assess this attentional bias. However, prior studies demonstrated poor psychometric properties of the SST. Methods We developed a modified Suicide Stroop Task (M-SST) and tested its psychometric properties in a sample of healthy controls (n = 30) and inpatients with STBs (n = 24). Participants (50% female, aged 18 to 61 years) completed the M-SST with neutral, positive, negative, suicide-related positive and suicide-related negative words. Interference scores were calculated by subtracting the mean reaction time (mean RT) of the neutral words from the mean RT of the suicide-related positive words (mean RTSuicide-Positive–mean RTNeutral) and suicide-related negative words (mean RTSuicide-Negative–mean RTNeutral), resulting in two suicide-specific interference scores. Similarly, interference scores were calculated for the positive and negative words by subtracting the mean RT of neutral words from the mean RT of positive and negative words. Results When analyzed separately, patients with STBs showed greater interferences for suicide-related positive words (p = 0.039), and for suicide-related negative words (p = 0.016), however, we found no group differences in interference scores for positive and negative words, suggesting a suicide attentional bias in patients with STBs. Controlling for the repeated measure design, a repeated measure ANOVA failed to detect a significant group × interference interaction effect (p = 0.176), which limits the generalizability of the findings. However, the interference score of suicide-related negative words showed an adequate classification accuracy (AUC = 0.72, 95% CI [0.58–0.86], p = 0.006) for differentiating between healthy controls and patients with STBs. Moreover, the interference scores showed acceptable internal reliability for the total sample and only suicide-related interference scores were correlated with clinical characteristics, thus demonstrating convergent validity. Conclusion The results provide preliminary evidence for a suicide attentional bias in individuals with STBs compared to healthy controls. The M-SST represents a promising tool for assessing a suicide attentional bias by revealing adequate psychometric properties. Future studies with larger samples are needed to confirm these preliminary findings.